HUBUNGAN PELAKSANAAN PERSONAL HYGIENE OLEH PERAWAT DENGAN TINGKAT KEPUASAN PASIEN IMOBILISASI DI RUANGAN MEDIKAL BEDAH RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2022 - Ginting, Amnita; Ernita Rante Rupang,; Lilis Novitarum,; Ruth Simarmata, (Jurnal Cakrawala Ilmiah, 2023)
Personal Hygiene is human self-care in maintaining their health to improve quality, health and safety. Due to health problems, it is possible that one or more of the patient's basic needs will be disturbed. This study aims to determine the relationship between the implementation of personal hygiene by nurses with the satisfaction level of immobilized patients in the surgical medical room at Santa Elisabeth Hospital Medan 2022. This type of research used a cross sectional design. The sampling technique in this study use purposive sampling involving 33 respondents. The instrument used is a personal hygiene questionnaire and a patient satisfaction questionnaire for immobilization. The results show that the implementation of personal hygiene category nurses carried out as much as 84.8% and patient satisfaction category satisfied as much as 75.8%. The results of the statistical test of the chi square test obtain a p-value of 0.000 (p <0.05) so it can be found that there is a significant relationship between the implementation of personal hygiene and the level of satisfaction of immobilized patients in the medical room of Santa Elisabeth Hospital Medan 2022. maintain the practice of personal hygiene in immobilized patients.